ANALISIS HUKUM TERHADAP SENGKETA JUAL BELI RUKO (STUDI KASUS PUTUSAN NO. 9/PDT.G/2019/PN.Mam): LEGAL ANALYSIS OF DISPUTES ON SHOP BUYING (CASE STUDY OF DECISION NO. 9/PDT.G/2019/PN.Mam) - Alvitra, Reskyta May; Taba, Hamzah; Juliati (Clavia, 2021)
Thisaresearch aims toadetermine and analyzeathe position of the shophouse sale and purchase agreement based on the loan agreement. As well as the reasons for the judge's consideration of buying and selling shophouses based on a loan agreement. This research uses normative legal methods or doctrinal legal research. This research is a type of legal research using secondary data or library research. This research was conducted at the Mamuju District Court. The source of this research data comes from primary data obtained from interviews with Judge Decision No. 9/PDT.G/2019/PN.Mam. Secondary data obtained by reviewing and looking for references, articles, legislation, and other sources related to the object under study. The results of this study indicate that the loan agreement and the sale and purchase agreement, in this case, are two different things but though they are related namely a loan agreement which is followed up with a sale and purchase agreement uppreviously there has been a criminal acts of fraud reporting by the Plaintiff allegedly committed by Defendant II, because the shophouse which was the object of the sale and purchase agreement that should have been owned by Plaintiff was blocked by Defendant I and Defendant III who based their statement acknowledged that he was the owner of the shophouse based on the Deed of Grant from Defendant II. The Judge's consideration in deciding the sale and purchase dispute is basically about the Control Against the Rights of 1 (one) building/shophouse unit carried out by the Defendants. The problem arose because Plaintiff was prevented from using the shophouse, because Defendant I admitted that the shophouse belonged to him based on the Deed of Grant. The Deed of Grant was made after the Sale and Purchase of shophouse was executed. In addition, the Deed of Grant which became the basis for the control of the shophouse was denied by Defendant II because the making of the Deed of Grant at the time it was signed was a blank. Thus, the Judge decided which stated that Plaintiff was the owner of the shophouse and the control of the shophouse by Defendant I and Defendant III was against the law.